Religious moderation understanding of islamic education teachers in SMA/SMK/MA in polewali mandar regency, west sulawesi - Sabara (Balai Diklat Keagamaan Ambon, 2023)
This paper aims to obtain a descriptive and ideographic description of the understanding of religious moderation among Islamic Religious Education (PAI) teachers at the senior high school (MA and SMA/SMK). Research problems include religious background, cases related to moderation, and patterns of understanding of religious moderation of PAI teachers. Religious moderation is described in three areas, namely understanding the diversity of religions and minority groups, the relationship between religion and the state, and the relationship between religion and culture. The research method is descriptive qualitative which makes the 25 PAI teachers as key informants who are interviewed in depth. The research location was in Polewali Mandar Regency, West Sulawesi Province. This study found that in general PAI teachers have traditional Islamic religious backgrounds, but have a low tendency of religious literacy, including literacy around religious moderation. There are two cases related to religious moderation in different contexts for PAI teachers. In the first case, a PAI MA teacher finally resigned as an ASN because he refused to salute the flag. Second, a non-ASN PAI MA teacher who is active in interfaith activities. In general, the pattern of understanding of religious moderation for PAI teachers (religion teachers) is relatively good, especially in terms of nationalism and culture. Relations in religious diversity need to be improved a little, especially with regard to understanding and tolerance towards adherents of other religions.